Moralitas, Pengendalian Internal Dan Gender Dalamkecenderungan Terjadinya Fraud - Luh Komang Merawati; I Nym Kusuma Adnyana Mahaputra (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
Morality, Internal Controland Gender in Fraud.University is an economicentity which is required to be accountable and transparent in funds management.Accountability can be indicated through financial reporting that is free from fraud.Fraud refers to the intentionally accountingerrors to mislead the financial statementreaders and usersin order to taking advantages. This research conducted with researchdesign experiments 2x2 factorial by adding a gender perspective in examining thetendency of commit accounting fraud between individuals who have a (high or low)level of moral reasoning and (with or without) elements of internal control organizationas factors that could cause accounting fraud. Data was analyze with two-waysANOVA and Mann Whitney test in testing hypotheses. Research results indicatesignificant differences in the tendency of the accounting fraud due to the level ofmorality, internal control and gender. The results of this study are expected to providerecommendations in evaluating internal control policy to prevent fraudulent accountingpractices and the importance of ethics and character education in the universityenvironment to reduce the intention of fraud.